Parity-specific weights for the Austrian Generations and Gender Survey - Isabella Buber (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2010)
The 'Generations and Gender Survey (GGS)' is an important data source for studying the dynamics of families and family relationships, it was out in Austria in 2008/09. After adjustment for age, sex, employment status, country of birth and living arrangements, we revealed a bias towards women with higher parities among the cohorts born until the mid- 1970s. Since parity is an important aspect for fertility analyses, weights were generated for the female sample that additionally adjust for the cohort-specific parity distribution. In this paper, we describe the original prevailing bias and inform the GGS user about the adjustment with the weights for the Austrian GGS. These weights are provided by VID to the international scientific community and are included in the Austrian GGS dataset.
Keywords: 300; Generations and Gender Survey; Austria; weights; parity distribution; Bevölkerungsstatistik; Kohortenanalyse; Statistische Verteilung; Österreich